The impact of progress indicators and information density on users' temporal perception and user experience in mobile pedestrian navigation applications - Li, Shasha; Lin, Zhongzhen (Displays, 2024)
•The type of progress indicator significantly influenced participants' duration perceptions.•The AOI significantly affects the participants' duration perception.•The “bar” type was significantly higher in learnability than the “countdown” type.•The participants preferred the “bar” type progress indicator, especially compared to the “pointer” type. This study examines progress indicators and information density in mobile pedestrian navigation applications and explores their impact on user duration perception and experience. The study attempted to improve the user's pedestrian navigation experiences through different interface visual design strategies. We conducted a 3 × 2 between-subjects analysis to evaluate the effect of progress indicators (bar, pointer, and countdown) and visual information (less and regular information) in a simulated pedestrian navigation application. Forty-eight subjects participated in a one-on-one manipulation experiment simulating walking a designated route, followed by duration judgments and scale surveys. The results showed that progress indicator types significantly influenced participants' duration perceptions. The duration perception of “less information” increased by nearly 26.3%, and the duration perception of “regular amount of information” decreased by almost 29%. In addition, participants experienced the progress “bar” type as having higher learnability. Finally, participants preferred the “bar” type progress indicator, and the information density did not affect their preferences.